The Structure and Crystallization Process of Amorphous Iron Nanoparticles - Thi Thanh, Duong; Mai An, Pham; Thi Thuy Trang, Giap; Thi Minh Thuy, Nguyen; Huu Kien, Pham (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3DO - 10.25073/2588-1140/vnunst.4891, 2019)
This paper studies the crystallization process and structure of amorphous iron nanoparticles by molecular dynamics method. The study shows that amorphous iron nanoparticles could not be crystallized at 300 K and 500 K. Iron nanoparticle, annealed at 900 K over a long time, was crystallized into a BCC crystal structure. The structure of crystallized iron nanoparticle at 900 K was analyzed through the pair radial distribution function and the number of crystal atoms upon various regions in nanoparticles. The simulation revealed that the first nuclei was formed most frequently in the area near the surface of the nanoparticle. Then the crystal cluster grew toward the centre of the nanoparticle. The completely crystallized nanoparticle had two components: the core with a BCC crystal structure and surface with an amorphous structure. As for the amorphous nanoparticle at 300 or 500 K, crystal-clusters were too small to grow large enough to crystallize the nanoparticle.   Keywords Iron nanoparticle, crystallize, annealing, crystal atom, crystal cluster. References [1] J.D. Honeycutt, C.H. Andersen, Molecular dynamics study of melting and freezing of small Lennard-Jones clusters, Journal of Physical Chemistry 91 (1987) 4950-4963. https://doi.org/ 10.1021/j100303a014. [2] H. Shin, H.S. Jung, K.S. Hong and J.K. Lee, Crystallization process of TiO2 nanoparticles in an acidic solution, Chemistry letters 33 (2004) 1382-1383. https://doi.org/10.1246/cl.2004. 1382. [3] D. Shi, Z. Li, Y. Zhang, X. Kou, L. Wang, J. Wang, J. Li, Synthesis and characterizations of amorphous titania nanoparticles, Nanoscience and Nanotechnology Letters 1 (2009) 165-170. https://doi.org/10.1166/nnl.2009.1037. [4] D.N. Srivastava, N. Perkas, A. Gedanken, I. Felner, Sonochemical synthesis of mesoporous iron oxide and accounts of its magnetic and catalytic properties, The Journal of Physical Chemistry B 106 (2002) 1878-1883. https://doi. org/10.1021/jp015532w. [5] N. Zaim, A. Zaim and M. Kerouad, The hysteresis behavior of an amorphous core/shell magnetic nanoparticle, Physica B: Condensed Matter 549 (2018) 102-106. https://doi.org/ 10.1016/j.physb. 2017.10.071. [6] L. Gao and Q. Zhang, Effects of amorphous contents and particle size on the photocatalytic properties of TiO2 nanoparticles, Scripta materialia 44 (2001) 1195-1198. https://doi.org/ 10. 1016/S1359-6462(01)00681-9. [7] G. Madras, B.J. McCoy, Kinetic model for transformation from nanosized amorphous TiO2 to anatase, Crystal growth & design 7 (2007) 250-253. https://doi.org/10.1021/cg060272z. [8] C.I. Wu, J.W. Huang, Y.L. Wen, S.B. Wen, Y.H. Shen, M.Y. Yeh, Preparation of TiO2 nanoparticles by supercritical carbon dioxide, Materials Letters 62 (2008) 1923-1926. https://doi.org/10. 1016/j.matlet.2007.10.043. [9] C. Pan, P. Shen and S.Y. Chen, Condensation and crystallization and coalescence of amorphous Al2O3 nanoparticles, Journal of crystal growth 299 (2007) 393-398. https://doi.org/ 10. 1016/j.jcrysgro.2006.12.006. [10] M. Epifani, E. Pellicer, J. Arbiol, N. Sergent, T. Pagnier, J.R. Morante, Capping ligand effects on the amorphous-to-crystalline transition of CdSe nanoparticles, Langmuir 24 (2008) 11182-11188. https://doi.org/10.1021/la801859z. [11] P.H. Kien, M.T. Lan, N.T. Dung, P.K. Hung, Annealing study of amorphous bulk and nanoparticle iron using molecular dynamics simulation. International Journal of Modern Physics B 28 (2014) 1450155 (17 page). https:// doi.org/10.1142/S0217979214501550. [12] V.V. Hoang and N.H. Cuong, Local icosahedral order and thermodynamics of simulated amorphous Fe. Physica B: Condensed Matter 404 (2009) 340-346. https://doi.org/10.1016/ j.physb. 2008.10.057.